2020
DOI: 10.1007/s00167-020-06247-3
|View full text |Cite
|
Sign up to set email alerts
|

No difference in functional outcomes, quality of life and survivorship between metal-backed and all-polyethylene tibial components in unicompartmental knee arthroplasty: a 10-year follow-up study

Abstract: PurposeThe purpose of this study was to compare functional outcomes, quality of life and survivorship at a minimum of 10 years postoperatively, between MB and AP tibial components in fixed‐bearing UKAs. MethodsA retrospective cohort study of 146 Query ID="Q3" Text="Author names: Please confirm if the author names are presented accurately and in the correct sequence (Lo Ngai Nung, Yeo Seng Jin). Also, kindly confirm the details in the metadata are correct." UKAs performed between 2004 and 2007 by a single fello… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…As regards the FJS-12, we compared the values collected at 12 and 24 months ( p = 0.401). Our data are comparable to those of other mUKA studies and better in some cases [ 57 , 58 , 59 , 60 , 61 ]. The mean satisfaction, rated from 1 to 10, was 9.32 ± 0.74.…”
Section: Discussionsupporting
confidence: 91%
“…As regards the FJS-12, we compared the values collected at 12 and 24 months ( p = 0.401). Our data are comparable to those of other mUKA studies and better in some cases [ 57 , 58 , 59 , 60 , 61 ]. The mean satisfaction, rated from 1 to 10, was 9.32 ± 0.74.…”
Section: Discussionsupporting
confidence: 91%
“…Another study found better KSSs and KOOSs and lower pain in MB-UKA than in AP-UKA patients at a follow-up of more than 10 years as well as no significant differences in knee range of motion [ 65 ]. Lee et al, employing PSM, did not report any statistically significant differences between MB-UKA and AP-UKA patients in terms of outcomes, quality of life, or 10-year implant survival [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Data analysis was performed using Microsoft Excel (2019) in conjunction with the XLSTAT resource pack (XLSTAT Premium, Addinsoft, New York, NY, USA). A propensity-score-matching (PSM) analysis was employed to minimize variations in known covariates between the cohorts [ 49 ], since several retrospective arthroplasty studies have used this type of analysis to minimize selection bias [ 8 , 27 , 50 57 ]. The two patient groups were matched one-to-one by an optimal matching algorithm [ 58 ].…”
Section: Methodsmentioning
confidence: 99%
“…When considering specifically conventional medial fixed‐bearing implants, literature has reported survivorship rates ranging from 89.5% to 96.0% at 10 years [15, 28]. A prospective, comparative study between all‐polyethylene versus metal‐backed tibial components, reported a survivorship of 92.3% and 91.1%, respectively [16]. The main reason for UKA revision reported by Lee et al was progression of OA, regardless of bearing design.…”
Section: Discussionmentioning
confidence: 99%